Rehabilitation of the beach at Teluk Cempedak, Pahang, using Pressure Equalisation Modules (PEM) system - Tan, King Seng (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/